2020
DOI: 10.1103/physrevd.101.024037
|View full text |Cite
|
Sign up to set email alerts
|

Growth of resonances and chaos for a spinning test particle in the Schwarzschild background

Abstract: Inspirals of stellar mass compact objects into supermassive black holes are known as extreme mass ratio inspirals. In the simplest approximation, the motion of the compact object is modeled as a geodesic in the space-time of the massive black hole with the orbit decaying due to radiated energy and angular momentum, thus yielding a highly regular inspiral. However, once the spin of the secondary compact body is taken into account, integrability is broken and prolonged resonances along with chaotic motion appear… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
46
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(51 citation statements)
references
References 55 publications
5
46
0
Order By: Relevance
“…As detailed e.g. in [25], the spin term in the MPT equations for such a background spacetime scales as…”
Section: Mpt Equations At Linear Order In the Spinmentioning
confidence: 92%
See 2 more Smart Citations
“…As detailed e.g. in [25], the spin term in the MPT equations for such a background spacetime scales as…”
Section: Mpt Equations At Linear Order In the Spinmentioning
confidence: 92%
“…The result applies in particular to Kerr spacetime, where it was shown that under the assumption of stationarity and axisymmetry only trivial mixed-symmetry Killing tensors exist which lead to products of known quasi-invariants. The absence of complete integrability in the sense of Liouville prevents us to rule out chaos at linear order in the spin, which is nevertheless suggested from the conclusions of [25,27,28]. An open question is how many of the two independent quasi-conserved quantities at linear order in the spin found by Rüdiger [22,23] admit a generalization that is conserved at quadratic order.…”
Section: Perspectivesmentioning
confidence: 99%
See 1 more Smart Citation
“…While analytical analysis of the dynamics of spinning binary tend to restrict the orbits to equatorial plane, where the spin is aligned or anti-aligned with the orbital angular momentum, the orbits can be complicated and even chaotic (see e.g. Suzuki & Maeda 1997;Hartl 2003a,b;Kao & Cho 2005;Zelenka et al 2019;Witzany et al 2019;Zelenka et al 2020) when the spin of the secondary is not aligned with the orbital angular momentum. The rich dynamical features of non-equatorial motions are studied by Singh, Wu & Sarty (2014); Han & Cheng (2017); Witzany (2019); Li, Wu & Singh (2019); Kimpson, Wu & Zane (2019); Keresztes & Mikóczi (2019); Keresztes & Mikoczi (2020), etc.…”
Section: Introductionmentioning
confidence: 99%
“…This reasoning holds away from the resonances, since the resonances are governed by the O S 2[26], which implies a contribution to the phase of order of radians.…”
mentioning
confidence: 99%